2014
DOI: 10.1068/p7673
|View full text |Cite
|
Sign up to set email alerts
|

Men's Facial Masculinity: When (Body) Size Matters

Abstract: Recent studies suggest that judgments of facial masculinity reflect more than sexually dimorphic shape. Here, we investigated whether the perception of masculinity is influenced by facial cues to body height and weight. We used the average differences in 3D face shape of 40 men and 40 women to compute a morphological masculinity score, and derived analogous measures for facial correlates of height and weight based on the average face shape of short and tall, and light and heavy men. We found that facial cues t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 32 publications
3
45
0
Order By: Relevance
“…By projecting high dimensional face data into a lower dimensional space, where each face is represented as an n-dimensional vector or projection, researchers can define axes in this space and compute the vector projection of where each face lies along this axis. This has been used successfully to produce image transforms based on the full range of data for a range of attributes, such as facial masculinity (Holzleitner et al, 2014; or body mass index (Henderson, Holzleitner, Talamas, & Perrett, 2016). Indeed, with this method, it is possible to select individuals who are facially objectively low or high on a trait, even if they are not rated as the highest or lowest in a dataset.…”
Section: Criticisms Of the 'Methods Of Extremes'mentioning
confidence: 99%
“…By projecting high dimensional face data into a lower dimensional space, where each face is represented as an n-dimensional vector or projection, researchers can define axes in this space and compute the vector projection of where each face lies along this axis. This has been used successfully to produce image transforms based on the full range of data for a range of attributes, such as facial masculinity (Holzleitner et al, 2014; or body mass index (Henderson, Holzleitner, Talamas, & Perrett, 2016). Indeed, with this method, it is possible to select individuals who are facially objectively low or high on a trait, even if they are not rated as the highest or lowest in a dataset.…”
Section: Criticisms Of the 'Methods Of Extremes'mentioning
confidence: 99%
“…Face-shape sexual dimorphism was measured from each photograph using a discriminant analysis method (Lee et al, 2014) and a vector analysis method (Holzleitner et al, 2014). These derive shape components from principal component analysis of landmarks to measure the probability of the face being classified as male (discriminant analysis method) or to locate the face on a female-male continuum (vector analysis method).…”
Section: Sexual Dimorphism Of Face Shapementioning
confidence: 99%
“…Studies on this topic typically employ two dimensional (2D) face images as stimuli (Coetzee et al, 2009(Coetzee et al, , 2010Re et al, 2013;Tinlin et al, 2013;Sell et al, 2008). However, some studies have used three dimensional (3D) face images because they may contain cues that are not captured well in 2D face images and, therefore, are likely to have greater ecological validity (Holzleitner et al, 2014;Re et al, 2012). The equipment needed to obtain high quality 3D face images is considerably more expensive than the equipment needed to obtain high quality 2D face images.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported positive correlations between measures of upper-body strength, such as handgrip strength, and perceptual judgments (i.e., ratings) of strength from both 2D face photographs (Sell et al, 2008) and 3D face images (Holzleitner & Perrett, 2016). Studies have also reported positive correlations between body mass index (BMI) and ratings of weight from 2D face photographs (Coetzee et al, 2009(Coetzee et al, , 2010Tinlin et al, 2013) and 3D face images (Holzleitner et al, 2014). Other studies have reported positive correlations between height and ratings of height from 2D face photographs (Re et al, 2013) and 3D face images (Re et al, 2012; but see also Holzleitner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation